THE EFFECT OF l SECURITIES lAND THE AMOUNT OF MONEY IN CIRCULATION ON ECONOMIC GROWTH IN INDONESIA - Sulaikha Amanda Putri; Syarifah Syafira (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study was conducted to examine the influence of financial instruments in the form of bonds and sukuk, as well as the circulation of money in the economy, on the level regarding indonesia’s economic growth. This research utilized secondary data with an observation period of 23 years, namely the period 2002–2024. Data regarding economic growth determined by gross domestic product (GDP) is obtained from the World Bank, while information related to bonds and sukuk was derived from data provided by the financial services authority. Data on the amount of money in circulation was acquired from the Central Statistics Agency. Multiple linear regression was the analytical method used in this study to ascertain how much the independent variables affected Indonesia's economic growth. The results of the study demonstrate that bonds, sukuk, and the quantity of money in circulation all significantly and favorably affect economic growth. Additionally, it has been demonstrated that these three factors taken together have a major impact on boosting national economic growth. Increases in the value of bonds, sukuk, and money in circulation can boost economic activity and bolster Indonesia's economic growth, according to this criterion.